Comparative analysis of phenolic content and antioxidative activities of eight Malaysian traditional vegetables - Nur Huda Faujan; Maryam Mohamed Rehan; Rahim Z.A.; Ahmad F.B.H. (Malaysian Society of Analytical Sciences, 2024)
Indexed by SCOPUS